AI and Qur’anic Interpretation: Exploring the Ethical and Epistemological Boundaries of Artificial Intelligence in Understanding the Qur’an - Alrumayh, Safa (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
The rapid development of Artificial Intelligence (AI) has significantly influenced religious studies, particularly in the analysis and interpretation of sacred texts. This study critically examines the role of AI in Qur’anic interpretation by addressing its epistemic capabilities, ethical limitations, and claims to interpretive authority. Employing a qualitative, literature-based research design, this study analyzes peer-reviewed scholarship on AI and religion, computational hermeneutics, natural language processing of sacred texts, and algorithmic bias, alongside classical and contemporary works in Islamic epistemology and Qur’anic exegesis. The findings indicate that while AI demonstrates high proficiency in linguistic processing, semantic consistency, and structural analysis of religious texts, it lacks epistemic understanding, moral intentionality, and ontological subjectivity. From the perspective of Islamic epistemology, knowledge is inseparable from consciousness, ethical responsibility, and interpretive accountability—dimensions that AI cannot possess. Moreover, algorithmic bias and the risk of decontextualization further challenge the use of AI as an autonomous interpretive authority in religious contexts. This study argues that AI should be positioned as an instrumental analytical tool rather than a subject of interpretation in Qur’anic exegesis. Its primary contribution lies in articulating a clear epistemological boundary between computational processing and hermeneutical understanding, thereby offering a critical framework for the ethical and responsible integration of AI within Islamic studies and religious scholarship more broadly.